Moderating effects of service separation on customer relationships with service firms: A social-exchange perspective - Alhathal, F.; Sharma, Piyush; Kingshott, Russel (Emerald Group Publishing, 2018)
Purpose: The purpose of this paper is to examine the impact of service separation on the ability of service firms to build and maintain customer relationships, by exploring the differences in the strength of interrelationships among key relational constructs between separated and unseparated service delivery modes. Design/methodology/approach: A field survey was conducted with retail banking customers in Saudi Arabia (n=592) using a structured self-administered questionnaire consisting of well-established scales. Data were analyzed using AMOS 24. Findings: Service separation negatively moderates (weakens) the ability of the service firms to leverage their social benefits, relational trust and affective commitment to increase customer loyalty and to strengthen overall customer relationships. Research limitations/implications: This study uses retail banking customers in Saudi Arabia to test the impact of service separation in their relationship with the bank; hence, its findings may not be generalizable to other types of services and cultural settings. Practical implications: Service firms using online and mobile technologies should be aware that trust and commitment remain key to building customer loyalty. Hence, the trade-off between the benefits of these technologies and their negative impact on customer relationship needs to be factored into managerial decision making. Originality/value: The paper highlights the importance of maintaining face-to-face interactions with service customers to create robust relationships that yield loyalty, despite the growing popularity of online and mobile technologies.